Penurunan Kadar Air Madu Dengan Dehidator Vakum - Johanes, Johanes; Kurniawan, Iwan; Yohanes, Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Vacuum dehydrator is an equipment that use to reduce water content in vacuum condition. The purpose of this experiment is to reduce water content of honey with pressure under 1 atm (vacuum condition) and heated. The heat controlled at 40oC. The experiment was done by reduce pressure until 7,385 kPa. It use time variable, those are 4, 8,12 hours. The result showed that at 12 hours experiment, get the lowest water content of honey is 18,18%. It lowest than 4 hours and 8 hours experiment result. Where initial water content before experiment is 23,2%. For a while, the resultof honey experiment at laboratory showed that water content of honey compactible with Indonesian Standard is less than 22%.Keywords : Vacuum Dehydrator, Honey, Heating Time